(untitled) (Nexo Revista Científica, 2021)
The primary purpose of the article is to examine the field oriented control system of permanent magnet synchronous machine (PMSM) electric drive with backup power supply. Authors propose to use bi-directional DC-DC converter to ensure the «hot» backup operation mode in case of grid fault. The change-over switching system, which provide transfer of voltage-source inverter (VSI) from DC link to the backup power source is considered. The presented system provides a good dynamic transient process; the results are confirmed by simulation in Psim software. Moreover, based on the results acquired, an electric drive based on PMSM with field oriented control and a backup power supply system from the battery via a bi-directional DC-DC converter is capable of operating according to the principles of «hot» backup.